An ISO/IEC/IEEE21451 Smart Sensor Network for Distributed Measurement of Pavement Structural Temperature. (9th March 2016) - Cai, Shuxiang; Yuan, Haiwen; Cui, Yong; Tian, Bo; Lv, Jianxun
An ISO/IEC/IEEE21451 smart sensor network for distributed measurement of pavement structural temperature (PST) is proposed in this paper. The proposed network architecture is a star network based on GPRS communication, adapting to the measurement environment of PST. The proposed network node consists of autonomous power supply system, network capable application processor (NCAP), and smart transducer interface module (STIM). The design of hardware and software is based on ISO/IEC/IEEE21451-1 and ISO/IEC/IEEE21451-2 standards. A human-computer interaction website is designed based on B/S three-layer architecture. Users having access rights can access the PST data using a browser connected to the internet. The proposed system has been used in the experimental research of the PST distribution of asphalt and cement pavement. The experimental results demonstrate that the proposed smart sensor network can adapt to the distributed fieldwork and unattended measurement environment of PST. The validity and reliability of the system have also been verified.